Simplifying evidence-based management of breast cancer-related lymphedema. Issue 5 (2nd September 2016) - Armer, Jane M.; Feldman, Joseph L.; Ostby, Pamela L.; Thrift, Kathryn M.; Lasinski, Bonnie B.; Beck, Marcia S.; Rodrick, Julia R.; Norton, Steve; Sun, Yuanlu; Udmuangpia, Tipparat; Armer, Nathan C.; Stewart, Bob R.
ABSTRACT: Introduction : This expert review examines the evidence base for lymphedema management and recommends ways to improve outcomes for breast cancer survivors at risk of and living with lymphedema through simplifying evidence-based self-management recommendations. Lymphedema risk-reduction and self-management behaviors can be complex and burdensome to survivors, underscoring the need for simplifying the self-management recommendations. Areas covered : Systematic reviews on complete decongestive therapy; complementary/alternative therapies; botanicals; exercise; surgical treatment; intermittent pneumatic compression therapy; psychosocial issues; self-management; and economic and health policy are summarized. Historic perspectives and future projections are presented. Expert commentary : The reviews establish the evidence base for the recommendations for simplification of self-management guidelines for persons at risk for and living with breast cancer-related lymphedema. Further research is needed to enhance levels of evidence for breast cancer-related lymphedema management. More rigorously-designed studies with larger samples, longer follow-up, and finely-tuned interventions and dosages are needed to extend our evidence base.